1880. Check if Word Equals Summation of Two Words
Description
The letter value of a letter is its position in the alphabet starting from 0 (i.e. 'a' -> 0
, 'b' -> 1
, 'c' -> 2
, etc.).
The numerical value of some string of lowercase English letters s
is the concatenation of the letter values of each letter in s
, which is then converted into an integer.
- For example, if
s = "acb"
, we concatenate each letter's letter value, resulting in"021"
. After converting it, we get21
.
You are given three strings firstWord
, secondWord
, and targetWord
, each consisting of lowercase English letters 'a'
through 'j'
inclusive.
Return true
if the summation of the numerical values of firstWord
and secondWord
equals the numerical value of targetWord
, or false
otherwise.
Example 1:
Input: firstWord = "acb", secondWord = "cba", targetWord = "cdb" Output: true Explanation: The numerical value of firstWord is "acb" -> "021" -> 21. The numerical value of secondWord is "cba" -> "210" -> 210. The numerical value of targetWord is "cdb" -> "231" -> 231. We return true because 21 + 210 == 231.
Example 2:
Input: firstWord = "aaa", secondWord = "a", targetWord = "aab" Output: false Explanation: The numerical value of firstWord is "aaa" -> "000" -> 0. The numerical value of secondWord is "a" -> "0" -> 0. The numerical value of targetWord is "aab" -> "001" -> 1. We return false because 0 + 0 != 1.
Example 3:
Input: firstWord = "aaa", secondWord = "a", targetWord = "aaaa" Output: true Explanation: The numerical value of firstWord is "aaa" -> "000" -> 0. The numerical value of secondWord is "a" -> "0" -> 0. The numerical value of targetWord is "aaaa" -> "0000" -> 0. We return true because 0 + 0 == 0.
Constraints:
1 <= firstWord.length,
secondWord.length,
targetWord.length <= 8
firstWord
,secondWord
, andtargetWord
consist of lowercase English letters from'a'
to'j'
inclusive.
Solutions
Solution 1: String to Number
We define a function \(\textit{f}(s)\) to calculate the numerical value of the string \(s\). For each character \(c\) in the string \(s\), we convert it to the corresponding number \(x\), then concatenate \(x\) sequentially, and finally convert it to an integer.
Finally, we just need to check whether \(\textit{f}(\textit{firstWord}) + \textit{f}(\textit{secondWord})\) equals \(\textit{f}(\textit{targetWord})\).
The time complexity is \(O(L)\), where \(L\) is the sum of the lengths of all strings in the problem. The space complexity is \(O(1)\).
1 2 3 4 5 6 7 8 9 10 |
|
1 2 3 4 5 6 7 8 9 10 11 12 13 |
|
1 2 3 4 5 6 7 8 9 10 11 12 13 |
|
1 2 3 4 5 6 7 8 9 |
|
1 2 3 4 5 6 7 8 9 10 |
|
1 2 3 4 5 6 7 8 9 10 11 12 13 14 |
|
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 |
|
1 2 3 4 5 6 7 8 9 10 11 12 |
|